OP0110 IXEKIZUMAB IMPROVES SIGNS AND SYMPTOMS OF PSORIATIC ARTHRITIS IN PATIENTS WHO HAVE HAD INADEQUATE RESPONSE TO 1 OR 2 TUMOR NECROSIS FACTOR INHIBITORS. (June 2019) - Bruce Kirkham, L; Sesin, Carlos; Sprabery, Aubrey Trevelin; Lin, Chen-Yen; Gellett, Amanda M.; Turkiewicz, Anthony
Abstract : Background: Psoriatic arthritis (PsA) is a progressive, chronic inflammatory disease often treated with tumor necrosis factor inhibitors (TNFi) when conventional treatments fail. Patients with inadequate response to TNFi represent a more difficult-to-treat population. Objectives: To report the efficacy of ixekizumab (IXE), a monoclonal antibody that selectively targets interleukin-17A, in patients with inadequate response to 1 TNFi or 2 TNFi. Methods: In a Phase 3 study (SPIRIT-P2; NCT02349295 ), patients who had an inadequate response or intolerance to 1 or 2 TNFi were randomized to receive subcutaneous IXE 80 mg every 2 weeks (IXEQ2W; N=123) or every 4 weeks (IXEQ4W; N=122), after a 160-mg starting dose, or placebo (PBO; N=118) for up to 24 weeks. At Week 16, patients not meeting predefined criteria (<20% improvement in tender joint count [TJC] and swollen joint count [SJC]) received rescue therapy and were imputed as nonresponders at Weeks 20 and 24. At Week 24, PBO patients were rerandomized to IXEQ2W or IXEQ4W through Week 52 and excluded from the 52-week analysis. At Week 32 or any subsequent visit, patients were discontinued if they did not reach ≥20% improvement from baseline in both TJC and SJC. These ad-hoc data were derived from patients in the intent-to-treat population with prior inadequate response to TNFi; intolerant patients were excluded from the analysis. Efficacy was measured by percentage of patients who attained ≥50% improvement in American College of Rheumatology response criteria (ACR50), an improvement in Health Assessment Questionnaire-Disability Index (HAQ-DI) ≥0.35, minimal disease activity (MDA), Disease Activity Score 28 – C-reactive protein (DAS28-CRP) EULAR Good Response criteria, and Disease Activity in Psoriatic Arthritis (DAPSA) ≤14. Results: At baseline, 1-TNFi inadequate responders were, on average, 52 years of age with a PsA diagnosis for 10 years; 40% were using MTX, and HAQ-DI was 1.2. 2-TNFi inadequate responders were 52 years of age with a PsA diagnosis for 11 years; 42% were using MTX, and HAQ-DI was 1.3. Regardless of inadequate response to 1 or 2 TNFi, at Week 24 significantly more patients receiving Q4W or Q2W than PBO attained ACR50, improvement in HAQ-DI ≥0.35, MDA, DAS28-CRP, and DAPSA ≤14. Improvement persisted on all measures through Week 52. Conclusion: Both IXE Q4W and Q2W improved the signs and symptoms of PsA in a population of difficult-to-treat patients who have had inadequate response to 1 or 2 TNFi. Disclosure of Interests: : L Bruce Kirkham Grant/research support from: Investigator for Janssen Research & Development, LLC, Consultant for: Abbvie, Eli Lilly and Company, Janssen, Novartis, Carlos Sesin Grant/research support from: Eli Lilly and Company, Novartis, Roche, Consultant for: Eli Lilly and Company, Novartis, Pfizer, Amgen, Abbvie, Janssen, Speakers bureau: Eli Lilly and Company, Novartis, Pfizer, Celgene, Abbvie, Amgen, Radius, Regeneron/Sanofi Genzyme, Janssen, Aubrey Trevelin Sprabery Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Chen-Yen Lin Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Amanda M. Gellett Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Anthony Turkiewicz Grant/research support from: Janssen, Eli Lilly and Company, UCB, Pfizer, Regeneron Sanofi-Genzyme, Novartis, Consultant for: Janssen, Eli Lilly and Company, UCB, Pfizer, Regeneron Sanofi-Genzyme, Novartis, Abbvie, Medac, Horizon, Genentech